Discriminatory Analysis of Biochip-Derived Protein Patterns in CSF and Plasma in Neurodegenerative Diseases - Rosen, Christoffer; Mattsson, Niklas; Johansson, Per M.; Andreasson, Ulf; Wallin, Anders; Hansson, Oskar; Johansson, Jan-Ove; Lamont, John; Svensson, Johan; Blennow, Kaj; Zetterberg, Henrik (Frontiers in Aging Neuroscience, 2011)
The role of biomarkers in neurodegenerative diseases has been emphasized by recent research. Future clinical demands for identifying diseases at an early stage may render them essential. The aim of this pilot study was to test the analytical performance of two multiplex assays of cerebral markers on a well-defined clinical material consisting of patients with various neurodegenerative diseases. We measured 10 analytes in plasma and cerebrospinal fluid (CSF) from 60 patients suffering from Alzheimer’s disease (AD), vascular dementia, frontotemporal dementia, dementia with Lewy bodies, or mild cognitive impairment, as well as 20 cognitively healthy controls. We used the Randox biochip-based Evidence InvestigatorTM system to measure the analytes. We found it possible to measure most analytes in both plasma and CSF, and there were some interesting differences between the diagnostic groups, although with large overlaps. CSF heart-type fatty acid-binding protein was increased in AD. Glial fibrillary acidic protein and neutrophil gelatinase-associated lipocalin in CSF and D-dimer in plasma were elevated in patients with cerebrovascular disease. A multivariate statistical analysis revealed that the pattern of analytes could help to differentiate the conditions, although more studies are required to verify this.